MANAJEMEN MODAL KERJA, MANAJEMEN SUMBER DAYA INSANI DAN PENDAPATAN WANITA PEDAGANG SAYUR KELILING - Andriani, Andriani (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2017)
Community economic activities will be well developed if accompanied by sound capital management and good insani resource management. Management processes that start from planning, organizing, implementing and controlling are the key to success of any micro, small, medium or large business. Working capital management is a management of current assets and liabilities. Working capital management has some important sense for the company. Firstly, working capital shows the size of the company's investment in current assets and claims on the company represented by current liabilities. Secondly, investment in assets liquidity, accounts receivable and inventory are sensitive to the level of production and sales. Insani resource management that is tabliq, sidiq, amanah, fatonah and istiqomah also have important role in realizing business goal that is profit and business survival